IDA a peptide ligand regulating cell separation processes in Arabidopsis - Aalen, Reidunn B (Journal of experimental botany, 2013)
In contrast to animals, plants continuously produce new organs, such as leaves, flowers, and lateral roots (LRs), and may shed organs that have served their purpose. In the model plant Arabidopsis thaliana the peptide INFLORESCENCE DEFICIENT IN ABSCISSION (IDA) signals through the leucine-rich repeat-receptor-like kinases (LRR-RLKs) HAESA (HAE), and HAESA-LIKE2 (HSL2) to control the abscission of floral organs after pollination. Recent work from other plant species indicates that this signalling system is conserved and could regulate leaf abscission in soybean and tomato. Abscission is a cell separation process involving the breakdown of cell walls between adjacent files of abscission zone (AZ) cells at the base of organs to be shed. The emergence of new lateral root primordia (LRP), initiated deep inside the root under the influence of the phytohormone auxin, is similarly dependent on cell wall dissolution to separate cells in the overlying tissues. It has been shown that this process also requires IDA, HAE, and HSL2. The receptors are redundant in function during floral organ abscission, but during lateral root emergence (LRE) they are differentially involved in regulating cell wall remodelling (CWR) genes. An overview is given here of the similarities and differences of IDA signalling during floral organ abscission and LRE